Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Law; Political Science
Keywords: FOUCAULT; Michel; 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

A New Alliance of De-legalisation and Legal Formalism? Reflections on Responses to the Social Deficit of the European Integration Project⋆ - Joerges, Christian (Law and Critique, 2008)
This paper will cover a wide range of issues. It will start with a reconstruction of the European Community’s ‘social deficit’, arguing that a credible response to this deficit would be a pre-condition for the democratic legitimacy of the deepened integration project. Such a response can be developed in a re-conceptualisation of European law as a new type of supranational/trans-statal conflict of laws – this is the thesis defended in the second section. This vision is contrasted in the third section, first with the steps towards Social Europe envisaged in the Draft Constitutional Treaty, and then with the messages of the recent judgments of the European Court of Justice (ECJ) in Viking and Laval. It goes without saying that the theoretical premises of the argument, let alone its many interdisciplinary dimensions and empirical background, can often only be signalled, but not developed systematically. " I wish to submit is that the ‘social embeddedness’ thesis can help us to understand why Europe has developed an ever more sophisticated regulatory machinery entrusted with the management of the internal market – and why the social deficit of the European construction has become a prominent part of the European agenda.
Law
Keywords: Social Europe; conflict of laws; ordoliberalism; social deficit; social embeddedness; socio-economic division; unity/diversity

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (Social Science Research Network, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Law; Sociology
Keywords: BLOCK; Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Law and Politics in Europe's Crisis: On the History of the Impact of an Unfortunate Configuration - Joerges, Christian (Constellations, 2014)
EXCERPT [KM]: Karl Polanyi has experienced a renaissance in recent years.13 We refer to his work in our remarks on the failures of the European project for three interrelated reasons: (1) Polanyi has underlined that modern markets were not generated by some evolutionary process but established by political planning.14 Europe's “internal market project” is the best conceivable confirmation of his thesis. (2) One of the most important insights of his work concerns the “social embeddedness” of markets and the economy.15 These insights are of crucial importance because Europe has on the one hand realized that the functioning of markets requires comprehensive regulatory activities but at the same time tends to disregard the economic, political and cultural variety and dependence of markets. (3) Polanyi can also provide clarity with regard to the growing skepticism about so many firmly held beliefs about the benefits of ever more European integration. EXCERPT 2: Led by the prompting of its highest court, Europe is waving the flag of economic freedoms of Europe's market citizens and is retreating from its commitment to collective labor law – once the institutionalized countermovement to the commodification of labor.1
Law; Political Science
Keywords: European Union; economic law; fictitious commodities; internal market project; social embeddedness

Reconfiguring the Politics–Law Relationship in the Integration Project through Conflicts–Law Constitutionalism - Everson, Michelle; Joerges, Christian (European Law Journal, 2012)
This paper argues that the relationship between law and politics must be reconfigured within the European Union. Dissecting recent crises in economic, social and political organisation within Europe with reference to the three ‘fictitious’ commodities of Karl Polanyi, we find that law in Europe has contributed to de-legalisation, de-socialisation and disenfranchisement. Moving on to review the potential for law to respond to crisis through new paradigms of conflict resolution as suggested by Ralf Dahrendorf, we find that the steering capacity of law is nevertheless limited if it fails to establish a sustaining relationship with politics. Our conclusions are modest: conflict–law constitutionalism cannot solve Europe's many crises. However, it does represent a new paradigm of law within which relations between European law and European politics might be re-established—a vital step to overcoming crisis.
Law
Keywords: European Union; constitutionalism; economic law; fictitious commodities

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Law; Political Science
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Informal Politics, Formalised Law and the ‘Social Deficit’ of European Integration: Reflections after the Judgments of the ECJ in Viking and Laval - Joerges, Christian; Rödl, Florian (European Law Journal, 2009)
The judgments of the European Court of Justice (ECJ) of December 2008 in Viking and Laval on the compatibility of national collective labour law with European prerogatives have caused quite a heated critical debate. This article seeks to put this debate in constitutional perspectives. In its first part, it reconstructs in legal categories what Fritz W. Scharpf has characterised as a decoupling of economic integration from the various welfare traditions of the Member States. European constitutionalism, it is submitted, is bound to respond to this problématique. The second part develops a perspective within which such a response can be found. That perspective is a supranational European conflict of laws which seeks to realise what the draft Constitutional Treaty had called the ‘motto of the union’: unitas in pluralitate. Within that framework, the third part analyses two seemingly contradictory trends, namely, first, albeit very briefly, the turn to ‘soft’ modes of governance in the realm of social policy and then, in much greater detail, the ECJ's ‘hard’ interpretations of the supremacy of European freedoms and its strict interpretation of pertinent secondary legislation. The conflict-of-laws approach would suggest a greater respect for national autonomy, in particular, in view of the limited EU competences in the field of labour law.
Law
Keywords: BLOCK; Fred; European Union; European constitutionalism; economic law; labour law; social embeddedness

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Law; Political Science
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy

A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Social Science Research Network, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Law
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity